Respuesta :

Answer: 1), 2) and 5) are equivalent.

Step-by-step explanation:

Since in first expression,  2+x=5 ⇒ x= 5-2= 3⇒x=3

In second expression, x+1=4⇒ x=4-1⇒x=3

In third expression,  9+x=6 ⇒ x=6-9⇒x= -3

in Fourth expression, x+(-4)=7 ⇒ x=7+4 ⇒ x=11

In fifth expression,  -5+x=-2⇒ x=-2+5 ⇒x=3

Thus, 1) 2) and 5) expression are giving the same result.

Therefore they are equivalent to each other.


Answer:

A, B, E on Edgen. Just took the test.

Step-by-step explanation:

2 + x= 5(A)

x + 1 = 4(B)

-5 + x = -2(E)